KAJIAN MUTU BUAH KELAPA SAWIT (Elaeis Guineensis Jacq.) PADA UMUR TANAMAN YANG BERBEDA DI KECAMATAN KUBU KABUPATEN ROKAN HILIR - Sinaga, Elfia Lasmaida; Khoiri, M. Amrul (SUNGKAI, 2025)
The low price of fresh fruit bunches (FFB) and poor fruit conditions such as the size of FFB and smaller oil palm fresh fruit in smallholder plantations in Kubu sub-district. This study aims to assess the quality of oil palm fruit at the age of 10, 15 and 20 years in Kubu District, Rokan Hilir Regency. The research was conducted in three locations based on the age of oil palm plants. This research was conducted using a survey method with data collection carried out by observation in the field and analysis in the laboratory. The parameters observed were fresh fruit weight, fresh fruit volume, mesocarp thickness, moisture content, free fatty acid content and gross content. The data obtained were analyzed with variance using SAS application, followed by DNMRT (Duncan's New Multiple Range Test) at the 5% level. Pearson correlation analysis was used to see the relationship between parameters. The results showed that 20 year old plants produced better fruit quality in physical conditions such as fresh fruit weight, fresh fruit volume, and higher mesocarp thickness compared to 10 and 15 year old plants.  The quality of oil palm CPO quality showed that 10, 15 and 20 years old plants were of good quality in accordance with SNI standards based on water content, free fatty acid content and gross content.